Positive changes among patients with advanced colorectal cancer and their family caregivers: a qualitative analysis. Issue 1 (2nd January 2017) - Mosher, Catherine E.; Adams, Rebecca N.; Helft, Paul R.; O'Neil, Bert H.; Shahda, Safi; Rattray, Nicholas A.; Champion, Victoria L.
Abstract : Objective: This study assessed positive changes in patients with advanced colorectal cancer and their family caregivers following diagnosis. We compared self-reported positive changes within patient-caregiver dyads as well as self-reports and patient reports of positive changes in caregivers. Design: Individual, semi-structured qualitative interviews were conducted with 23 patients with advanced colorectal cancer and 23 caregivers. A theoretical thematic analysis of interview transcripts was framed by posttraumatic growth theory. Results: Patients and caregivers described five positive changes: closer relationships with others, greater appreciation of life, clarifying life priorities, increased faith, and more empathy for others. Additionally, only caregivers reported better health habits following the cancer diagnosis, and a minority of patients and caregivers reported no positive changes. In about half of cases, patients reported at least one positive change that was identical to that of their caregiver. However, in most cases, patient and caregiver reports of the caregiver's positive change were discrepant. Conclusion: Findings suggest that positive changes are a shared experience for many patient-caregiver dyads and obtaining both patient and caregiver reports of caregiver positive changes provides a more comprehensive understanding of their experience. Interventions may capitalise on positive changes to promote meaningful living in the context of advanced cancer.